H3K9me3 demethylation by JMJD2B is regulated by pirfenidone resulting in improved NASH - J. Samael Rodriguez-Sanabria; Rebeca Rosas-Campos; Ángel Vázquez-Esqueda; Ivonne Palacios-Marín; Josep Jiménez-Chillaron; Rebeca Escutia-Gutiérrez; Luis Felipe Jave-Suarez; Marina Galicia-Moreno; Hugo Christian Monroy-Ramirez; Eira Cerda-Reyes; Mónica Almeida-López; Erika Martinez-Lopez; et al. (Scientific Reports, 2024)
Abstract NASH is characterized by hepatic lipid accumulation and inflammation; and JMJD2B—a histone demethylase—upregulation has been linked to its progression. Pirfenidone (PFD) is an antifibrotic agent with anti-inflammatory and antioxidant effects recognized to decrease NASH symptoms. Herein, our aim was to investigate PFD-induced epigenetics mechanisms involving JMJD2B and histone modifications in experimental NASH. Male C57BL/6J mice were fed with normo-diet, or high fat/carbohydrate diet (HF) for 16 weeks. A HF-subgroup was treated with PFD 300 mg/kg/d from week 8th to the end of protocol. Insulin tolerance test and liver and fat histological and biochemical analyses were carried out. Hepatic transcriptome was examined. Liver proteins were studied by western blot (WB) and Chromatin immunoprecipitation. In vitro, lipotoxicity was induced in HepG2 cells and proteins were evaluated using WB. Molecular docking was used to explore binding of PFD to JMJD2B. Mice treated with PFD reduced weight gain, epididymal fat and inflammatory nodules, and steatosis in liver tissue, as well as, improved biochemical test. PFD modified the expression of Jmjd2b, Pparg, Fasn and Srebp1, and restored JMJD2B protein and H3K9me3 repressive mark, both in animal and cell models. PFD increased hepatic enrichment of H3K9me2 and H3K9me3 at the promoter region of Fasn and Srebp1, and Pparg. In HepG2 cells, PFD reduced lipid vacuole accumulation. In silico, PFD interacted with JMJD2B catalytic site. PFD is an epigenetic regulator modifying JMJD2B activity, resulting in reduced NASH traits.